Supplier selection for agile supply chain - Mesfer, Abdullah Hamed Farag (Kulliyyah of Engineering, International Islamic University Malaysia, 2021)
This research examines the selection of suppliers as they are one of the most main important elements of any supply chain. Due to the importance, different aspects of supply chain types and possible mathematical methods have been addressed to select suppliers under predetermined factors and criteria which are followed by all suppliers. A weighted linear model was proposed to solve the problem of supplier selection inspired by multi-criteria decision making. DEA consists of a programmable mathematical approach that enables to evaluate the efficiency and performance of decision-making units successfully with identical inputs and outputs. Considering that different suppliers are available to the company, the manager should make a decision as to who is the best supplier based on their valuations and considered several criteria. Based on the comparison, the main factors can be considered to examine the resulting changes in the findings through the DEA model. The priority of measures can be changed by swapping their order to consider different importance sequences. Recently, organizations are moving towards a reduction in the number of suppliers since it is difficult to manage a large number of them. The reason for this research lies in the development of an evaluation and selection model for suppliers, which is effective and comprehensive. Improving the efficiency and effectiveness of public supply chains processes is an essential part of an organization's ability to compete effectively. Therefore, the main objective of this research is to plan and develop a system to solve problems of selection of suppliers. The model created here is application particular for a manufacturing company. Research is therefore required to distinguish general models that are applicable for various organization types. The utilization of the show strategies likewise needs a lot of research as it might get complex with objectives more than one.